Legal Consequences of Mock Transactions - Kossak, Volodymyr; Yakubivskyi, Ihor; Oprysko, Mykola; Tsikalo, Volodymyr; Bek, Yulian (International Journal of Criminology and Sociology, 2022)
In order to increase the material benefits, in order not to pay taxes or to pay less, in order to conceal information and for other purposes, the parties entering into legal relations become participants in mock transactions. The practise of mock transactions is to replace the conclusion of a single document, such as a sale one, with the conclusion of a contract of charitable contribution. The practise of using mock transactions is quite common and it is almost impossible to prove the nature of the transaction. Therefore, this work is aimed at investigating the institution of the mock transaction, as well as to develop recommendations for the practical application of the rules governing this institution. To conduct this study, the materials of the practise of dispute resolution on the application of the consequences of fictitious transactions by the courts of Ukraine, the dialectical method of cognition, the formal-legal method, the hermeneutic-legal method were used. As a result of research the signs of mock transactions, approaches of detection of fictitious transactions are established. It can be concluded that the distinguishing feature of fictitious and mock transactions is the orientation of the will of the parties to the transaction on the occurrence of legal consequences.